2016
DOI: 10.1080/13803395.2016.1163327
|View full text |Cite
|
Sign up to set email alerts
|

New ways to analyze word generation performance in brain injury: A systematic review and meta-analysis of additional performance measures

Abstract: The potential of additional performance measures is not yet fully exhausted in patients with brain injury. The temporal measure of response latencies in particular is not adequately represented, though it may be a reliable measure especially for identifying subtle impairments. Unfortunately, there is no general consensus as of yet on which additional measures are best suited to characterizing word generation performance. Further research is needed to specify the additional parameters that are best qualified fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(51 citation statements)
references
References 79 publications
(239 reference statements)
1
49
0
1
Order By: Relevance
“…) and of a variety of neuropsychiatric diagnoses (reviewed in Thiele et al . ). Even mildly impaired PWA (WAB‐R AQ > 80) demonstrated diminished verbal fluency scores (table ), indicating the sensitivity of verbal fluency measures to the presence of mild aphasia.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…) and of a variety of neuropsychiatric diagnoses (reviewed in Thiele et al . ). Even mildly impaired PWA (WAB‐R AQ > 80) demonstrated diminished verbal fluency scores (table ), indicating the sensitivity of verbal fluency measures to the presence of mild aphasia.…”
Section: Discussionmentioning
confidence: 97%
“…In a meta‐analysis of verbal fluency measures, Thiele et al . () found that clustering and perseverations had larger effect sizes than other response analyses. Very little is known about these measures in PWA, except that, for animal fluency, PWA produce smaller cluster sizes, pause longer between clusters and produce fewer clusters than neurotypical adults (Bose et al .…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations